Engineering design - Dieter, George E. , 1928-; Schmidt, Linda C.
"Preface to sixth edition the sixth edition of Engineering Design continues the reorganization and expansion of topics introduced in the fourth edition. Major reorganization of topics to improve flow of information and increase learning have been made in Chapter 3, Problem and Need Identification; Chapter 6, Concept Generation; and Chapter 7, Decision Making and Concept Selection. A new, progressive example has been introduced and is continued through these three chapters. A new Chapter 10, Design for Sustainability and the Environment, has been added. The book continues its tradition of being more oriented to material selection, design for manufacturing, and design for quality than other broad-based design texts"-- Provided by publisher